Design and Experimental Validation of Linear and Nonlinear Digital Synthetic Impedances for Electromechanically Coupled Systems - Silva, Tarcísio Marinelli Pereira; Clementino, Marcel Araújo; Sousa, Vagner Candido de [UNESP] (Springer Nature, 2022)
Purpose: This study reports on shunt circuits enabled by low-cost, small-scale electronic circuitry and free software by combining piezoelectric materials and digital devices. This class of systems can be considered in many different vibrating problems, such as elastic and aeroelastic structures and metastructures, aiming for adaptive and reconfigurable vibration attenuation capabilities. Methods: A general electronic circuit that suits for different vibration control techniques in electromechanically coupled systems is presented, while the specific technique emulation is achieved via software programming, so that the same hardware works for different techniques. Results: The proposed method successfully reproduces the electrical impedance across the electrodes of a piezoelectric material obtained with consolidated analog techniques such as linear resistive shunt (R) and resistive–inductive shunt (RL), and also the nonlinear synchronized switch damping on short circuit (SSDS) and synchronized switch damping on inductor (SSDI). Conclusions: The performance of the proposed digital platform is comparable to experimental data and circuit simulation obtained with analog circuits for validation for both the linear (R and RL) and the nonlinear (SSDS and SSDI) techniques. The proposed platform can be extended and applied to many different vibration control systems with electromechanical coupling.
Keywords: Adaptive damping techniques; Electromechanically coupled systems; Synthetic impedance circuits; Vibration control